Historical monuments and tourist sights in the north of Oltenia [slides]. (Bucuresti Anima Film, 1974)
Shows numerous architectural monuments in the Romanian region.
Text indicates 60 slides. Library has 53 slides only.
Keywords: Monuments -- Romania -- Oltenia; Architecture; European history